Peningkatan Kemampuan Pemahaman Konsep Matematika melalui Pembelajaran Berbasis Masalah Berbantuan Lembar Kerja Siswa - Sri Wening Handriastuti; Nizaruddin Nizaruddin; Evi Suprihatin Handayani; Muhammad Saifuddin Zuhri (Journal on Education, 2024)
This research is classroom action research which aims to improve student ability to understand mathematic conceps. The research object was SMA N 8 Semarang with the research subject being class XI-03 students. Data is collected through tests and observations. The results of the research show that class XI-03 students' understanding of mathematical concepts has increased in each cycle. At the pre-cycle stage, understanding of mathematical concepts reached 25.7143%. Then, in cycle I it reached 66.8571% achieving learning completeness with an average value of 66.8571 and cycle II reached 85.7143% with an average value of 86. From the results of this research it can be concluded that problem-based learning assisted by LKS can improve students' ability to understand mathematical concepts.